(untitled) (Comparative Professional Pedagogy, 2024)
Content and Language Integrated Learning (CLIL) is an educational approach that simultaneously teaches a non-language subject and a foreign language, enhancing both content knowledge and language skills. Originating in Europe, CLIL focuses on the 4Cs: content, communication, cognition, and culture, ensuring balanced subject matter and language proficiency. CLIL is distinct from bilingual or immersion education by its integrated approach. The Council of Europe supports CLIL to promote multilingualism and improve curricula quality. This study aims to analyze the foreign experience with CLIL, explore its didactic potential, and evaluate its implementation prospects in Ukraine. CLIL is characterized by integrating subject content with language learning, fostering language development through meaningful contexts, and enhancing cognitive skills like critical thinking and problem-solving. It also promotes cultural awareness and can be adapted to various educational contexts and proficiency levels. It has been defined that effective CLIL implementation requires trained teachers and appropriate materials. The methodology has spread across Europe, with various models tailored to different educational contexts. The Adjunct Model integrates language learning with subject teaching, the Embedded Model fully integrates language and content, and the Dual-Focus Model balances content and language objectives. Successful examples include bilingual schools in Hungary and long-standing practices in Bulgaria. The advantages of CLIL’s implementation have been defined. They include increased motivation, contextual language learning, preparation for a globalized world, and enhanced language proficiency. It also promotes content knowledge alongside language skills, offers international opportunities, and bridges language and content classes. However, challenges include the need for trained teachers, balancing content and language instruction, resource limitations, and large class sizes. Overcoming these challenges involves professional development, collaboration, material development, gradual integration, and using technology. The conclusion has been formulated that CLIL enhances language skills and subject knowledge, transforming educational approaches and improving learning outcomes.